Latent autoimmune diabetes in adults in China - Qiu, Junlin; Xiao, Zilin; Zhang, Ziwei; Luo, Shuoming; Zhou, Zhiguang (Frontiers in Immunology, 2022)
Latent autoimmune diabetes in adults (LADA) is a type of diabetes caused by slow progression of autoimmune damage to pancreatic beta cells. According to the etiological classification, LADA should belong to the autoimmune subtype of type 1 diabetes (T1D). Previous studies have found general immune genetic effects associated with LADA, but there are also some racial differences. Multicenter studies have been conducted in different countries worldwide, but it is still unclear how the Chinese and Caucasian populations differ. The epidemiology and phenotypic characteristics of LADA may vary between Caucasian and Chinese diabetic patients as lifestyle, food habits, and body mass index differ between these two populations. The prevalence of LADA in China has reached a high level compared to other countries. The prevalence of LADA in China has reached a high level compared to other countries, and the number of patients with LADA ranks first in the world. Previous studies have found general immune genetic effects associated with LADA, but some racial differences also exist. The prevalence of LADA among newly diagnosed type 2 diabetes patients over the age of 30 years in China is 5.9%, and LADA patients account for 65% of the newly diagnosed T1D patients in the country. As a country with a large population, China has many people with LADA. A summary and analysis of these studies will enhance further understanding of LADA in China. In addition, comparing the similarities and differences between the Chinese and the Caucasian population from the perspectives of epidemiology, clinical, immunology and genetics will help to improve the understanding of LADA, and then promote LADA studies in individual populations.